A dynamic pricing scheme for electric vehicle in photovoltaic charging station based on Stackelberg game considering user satisfaction. (April 2021) - Dai, Yeming; Qi, Yao; Li, Lu; Wang, Baohui; Gao, Hongwei
Highlights: A Stackelberg game considering the correlation among multi-time slots is proposed. The time interval is divided into charging time interval and pricing time interval. User satisfaction is added to the game model. The game model with uncertainty is transformed into a convex optimization problem. Abstract: Electric vehicle (EV) has increasingly become an important part of the load of smart power grid in recent years. Since uncoordinated EV would stress the distributed grid system, the establishment of Photovoltaic (PV) charging station is of great significance to optimizing domestic power demand and developing a low-carbon society. In this paper, a dynamic pricing scheme based on Stackelberg game for EV charging station with PV system is proposed. Considering the uncertainty of electricity changes before and after charging, we divide one day into two kinds of time intervals: charging time interval and pricing time interval, and the demand response (DR) based on preference of EV user is also implemented. Moreover, the constraint reflecting the fluctuation (uncertainty) of power consumption caused by the charging continuity of EV is also introduced to the model. By analyzing the probability property of constraints, the game model with uncertainty is equivalently transformed into a convex game at the end. Additionally, the existence and uniqueness of Stackelberg Equilibrium (SE) is proved, so the optimal strategies of all participants are guaranteed. Finally, a distributed algorithm is designed to obtain the SE. The simulation results show that the pricing scheme proposed in this paper can better reduce the selling price of charging station and increase the profit of charging station.